EFEKTIFITAS ARANG TEMPURUNG KELAPA (Cocus nucifera L) DALAM MENURUNKAN KESADAHAN TOTAL PADA AIR - rafidah rafidah; elsa safitri muin (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2019)
ABSTRACT  One of the chemical parameters in the water requirement is water hardness. Hardness is the term used in water containing the cation causing hardness. In general, hardness is caused by the presence of metals or cations of divalent 2, such as Fe, Sr, Mn, Ca and Mg.The purpose of this research is to know how the effectiveness of coconut shell charcoal in reducing total hardness in water. The type of research conducted is True Experiment with Pretest - Posttest Group Design design that is comparing the decrease of water hardness before and after being treated with coconut shell charcoal medium by using combination of thickness variation and contact time.Based on this research it is known that there is relationship between thickness variation and contact time with decrease of total hardness in water. With the result that is at 10 cm thickness by using time variation 40,50, and 60 minutes obtained by sequence 7.82%, 11.25% and 12.5%. As for the thickness of 20 cm with variations of time 40 minutes, 50 minutes, and 60 minutes obtained results 8.75% sequence, 13.76% and 19.16%. While at 30 cm thickness with time 40 minutes, 50 minutes, 60 minutes sequentially obtained results 22.05%, 27.08% and 33.33%.            The conclusion of this research is the variation of thickness and contact time of charcoal and water of sadah able to decrease the hardness. So it can be an alternative in reducing hardness. For further researchers can use or combine other media so that the results of hardness filtration can occur decrease the hardness. Keyword: Hardness, Coconut Shell Charcoal, Charcoal Thickness, Contact Time